Intravenózní leiomyomatóza jako vzácný nádor myometria - Regász, V; Boháč, V; Rychnovský, J (Ceska gynekologie, 2018)
AIM: To present a case of a woman diagnosed with intravenous leiomyomatosis of the uterus. TYPE OF STUDY: Case report. SETTING: Department of Obstetrics & Gynaecology, Středomoravská nemocniční a.s., Přerov Hospital. CASE REPORT: A 39-year old woman was referred to our unit with uterine fibroids, dysfunctional uterine bleeding and anaemia. Abdominal hysterectomy was performed. The histopathological analysis diagnosed the presence of intravenous leiomyomatosis. After a thorough literature review, we decided to perform an adnexectomy. It was not possible to perform this laparoscopically due to adhesions from previous operation. A conversion to open surgery was necessary. CONCLUSION: Intravenous leiomyomatosis is a rare clinical condition characterised by the ability of the leiomyoma to spread outside the uterus via the venous system. The diagnosis is difficult to obtain and can only be made after histopathological examination. There are no universal treatment guidelines in place at present.
Keywords: Myometrium; nádory dělohy; intravenous leiomyomatosis; Pregnancy; vaskulární nádory; Humans; myometrium; Leiomyomatosis; Female; dospělí; Leiomyoma; leiomyomatóza; leiomyom; lidé; Uterine Neoplasms; hysterectomy adnexectomy.; Adult; ženské pohlaví; těhotenství; Vascular Neoplasms; surgical treatment; myoma/leiomyoma/fibroid